The Influence of Goal Setting Autonomy and Commitment to Organization Goals on Performance: A Mediation Moderation Model - Gibb J; Billinger S; Haar J (Springer Science+Business Media, LLC, 2026)
This study examines the influence of goal setting autonomy (GSA) and commitment to organization goals (COG) on financial performance. We develop and test hypotheses using a rich dataset of 209 salespersons and their managers’ participative goal setting practices in a complex multi-task sales environment in the New Zealand real estate industry. In this industry, managers attempt to motivate workers by using autonomy in setting performance goals. Using Structural Equation Modelling (SEM), we find that both GSA and COG encourage worker behaviour towards performance. Our data also reveals that GSA and COG can have a detrimental effect on workers’ attitude and effort towards some individual job tasks that in turn can have negative performance implications. By providing a micro-level understanding of how GSA and COG motivate a worker’s attitude and effort toward individual job tasks, we shed light on the importance of capturing and managing knowledge that managers need, to effectively grant workers more autonomy in goal setting. Our results thereby reveal unexpected limits of GSA as a design choice for managers or organizations that seek to decentralize decision making.
Keywords: Knowledge management; Organization design; Decentralization; Participative goal setting; Work effort; Work attitude